Conditioning to Enhance the Effects of Repetitive Transcranial Magnetic Stimulation on Experimental Pain in Healthy Volunteers - Proulx-Bégin, Léa; Herrero Babiloni, Alberto; Bouferguene, Sabrina; Roy, Mathieu; Lavigne, Gilles J.; Arbour, Caroline; De Beaumont, Louis (Frontiers in Psychiatry, 2022)
Objective: In this proof-of-concept study we sought to explore whether the combination of conditioning procedure based on a surreptitious reduction of a noxious stimulus (SRPS) could enhance rTMS hypoalgesic effects (i.e., increase heat pain threshold [HPT]) and augment intervention expectations in a healthy population. Methods: Forty-two healthy volunteers (19-35 years old) were enrolled in a randomized within-person crossover-controlled study and were assigned to one of two groups: 1) SRPS and 2) No SRPS. Each participant received two consecutive sessions of active or sham rTMS over the M1 area of the right hand on two visits 1) active, 2) sham rTMS) separated by at least one-week interval. HPT and the temperature needed to elicit moderate heat pain were measured before and after each rTMS intervention on the right forearm. In the SRPS group, conditioning consisted of deliberately decreasing thermode temperature by 3°C following intervention before reassessing HPT, while thermode temperature was held constant in the No SRPS group. Intervention expectations were measured before each rTMS session. Results: SRPS conditioning procedure did not enhance hypoalgesic effects of rTMS intervention, neither did it modify intervention expectations. Baseline increases in HPT were found on the subsequent intervention session, suggesting variability of this measure over time, habituation or a possible “novelty effect”. Conclusions: Using a SRPS procedure in healthy volunteers did not enhance rTMS modulating effects on experimental pain sensation (i.e., HPT). Future studies are therefore needed to come up with a conditioning procedure which allows significant enhancement of rTMS pain modulating effects in healthy volunteers.